Pioneers of Capitalism – A Response - Prak, Maarten; van Zanden, Jan Luiten (TSEG - The Low Countries Journal of Social and Economic History, 2024)
The aim of Pioneers of Capitalism was to provide a synthesis of the research that has been done over the past 25 years by the Utrecht social and economic history group, in particular, and by scholars in this field more generally. The framework was the capitalism debate that has received much attention recently. What does the Dutch case tell us about capitalism as an economic and socio-political system?